Regulacja Stanu Deformacji w Płaskich Ustrojach Prętowych - Holnicki-Szulc, J. (Engineering Transactions, 1973)
The aim of the paper is to formulate the problem of introducing initial strains (distortions) lo plane rod structures, and to create a certain state of initial stresses. This may prove useful in the problems of regulation (control) of the state of strain of structures subject to external loading. The equations governing the plane elasticity problem of continuous lattice models with distortions are derived. Formulated is also the problem of a suitable selection of the distortion field leading to such final states of stress which satisfy certain control condition - for instance, the minimum of total stressing of the system. A rotationally symmetric case is presented as an example.